Hubungan Dukungan Keluarga dengan Kualitas Hidup Penderita Tuberkulosis - Candra Saputra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Tuberculosis (TBC) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The phenomenon that is found in today's society is that there are still family members who are afraid to be close to someone who has tuberculosis, so that excessive caution appears, for example, such as alienating the patient, reluctant to talk, and if close the patient will immediately cover his nose and so on. This study aims to determine